Traditional Methods of Teaching Foreign Languages (Eurasian Journal of Learning and Academic Teaching, 2022)
The history of foreign language teaching methods knows numerous and varied attempts to find the most rational method of teaching foreign languages. The most ancient was the natural method, which was no different from the method by which a child is taught his native language. A foreign language was mastered by imitation of ready-made samples, by repeated repetition and reproduction of new material by analogy with the studied one